Aktivitas Antioksidan dan Tabir Surya Ekstrak Daun Gyrinops versteegii (Antioxidant activity and Sunscreen of Gyrinops versteegii Leaf Extract) - Maeda Wahyuningrum; Rita K Sari; Mohamad Rafi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
The aim of this study was to determine the yield and phytochemicals, antioxidant activity, and sunscreen of the Gyrinops versteegii leaf extracts. The leaf simplicia was extracted using soxhletation method  with   multilevel polarities  of solvent (n-hexane, ethyl acetate, and metanol). The analysis of phytochemical extracts has been carried out the qualitatively and quantitatively. The antioxidant activity testing was performed in vitro through the effective concentration (EC50) extract in capturing DPPH radicals. Sunscreen activity has been done through testing sun protection factor (SPF). The result showed that the  yield of n-hexane extract, ethyl acetate, and methanol extracts  were 7.83, 5.46, and 6.77% respectively. The phytochemical analysis showed that  the ethyl acetate and methanol extracts were strongly detected containing antioxidant compounds such as p-hydroquinone, flavonoid, and tannins with the total phenol of the  ethyl acetate and methanol extracts  were 3.40 and 4.27% respectively. The n-hexane extract detected contains weakly the antioxidant compounds with  the total phenol was 0.45%.  The methanol extract is the highest antioxidant activity  (EC50 14.46 μg ml-1) and has ultra sunscreen activity (SPF>15).